Brand Experience Affects Brand Attitude, Brand attachment, Brand Satisfaction, and Brand Loyalty On Customer Make Over - Rakhmawati, Heni; Tuti, Meylani (JDM (Jurnal Dinamika Manajemen), 2023)
This study aims to identify the relationships between brand experience and brand attitudes, brand attachment, brand satisfaction, and brand loyalty. 177 Consumers of Make Over make up the study’s sample. The sampling strategy employs purposive sampling by choosing a sample that only consists of users of Make Over goods. The validity and dependability of the data were examined. a technique for data analysis that fuses quantitative and descriptive approaches. A structural equation model (SEM) was used in the analysis of quantitative data utilizing smart PLS software. The brand experience of Make Over cosmetic items, according to the study, influences how consumers build brand attitudes, brand attachment, brand satisfaction, and brand loyalty in both a direct and indirect manner. The findings of this study suggest that consumer experience with a brand might influence attitudes toward the brand and make consumers more loyal to it. Brand loyalty will ultimately be fueled through attachment, which will boost satisfaction. This study advances the field of brand lit- erature. Researchers and vendors can learn from this study about how to strengthen brands. Further investigation on individuals and makeup artists with a focus on individual users is advised because the survey’s responses were all from the Jakarta region and only included individual users.